Genetic diversity of Leptospira isolates in Lao PDR and genome analysis of an outbreak strain - Grillová, L; Robinson, MT; Chanthongthip, A; Vincent, AT; Nieves, C; Oppelt, J; Mariet, J-F; Lorioux, C; Vongsouvath, M; Mayxay, M; Phonemeexay, O; Rattanavong, S; et al. (Public Library of Science, 2021)
Background Although Southeast Asia is one of the most leptospirosis afflicted regions, little is known about the diversity and molecular epidemiology of the causative agents of this widespread and emerging zoonotic disease. Methodology/Principal findings We used whole genome sequencing to examine genetic variation in 75 Leptospira strains isolated from patients in the Lao PDR (Laos) between 2006 and 2017. Eleven serogroups from 4 Leptospira species and 43 cgMLST-defined clonal groups (CGs) were identified. The most prevalent CG was CG272 (n = 18, 26.8%), composed of L. interrogans serogroup Autumnalis isolates. This genotype was recovered throughout the 12-year period and was associated with deaths, and with a large outbreak in neighbouring Thailand. Genome analysis reveals that the CG272 strains form a highly clonal group of strains that have, for yet unknown reasons, recently spread in Laos and Thailand. Additionally, accessory genes clearly discriminate CG272 strains from the other Leptospira strains. Conclusions/Significance The present study reveals a high diversity of Leptospira genotypes in Laos, thus extending our current knowledge of the pan- and core-genomes of these life-threatening pathogens. Our results demonstrate that the CG272 strains belong to a unique clonal group, which probably evolved through clonal expansion following niche adaptation. Additional epidemiological studies are required to better evaluate the spread of this genotype in Southeast Asia. To further investigate the key factors driving the virulence and spread of these pathogens, more intense genomic surveillance is needed, combining detailed clinical and epidemiological data.